Pregnancy and its Outcomes in Polycystic Women Treated with Metformin and Ovulation Induction Medicines - AsmaIrfan,IrfanAfzalMughal ,GulleAtif; Abida Sultana, Afifa Kulsoom, Rahim Iqbal (Journal of Rawalpindi Medical College, 2014)
Background: To study the effectiveness of Metformin in attaining pregnancy along with ovulation induction medicines in infertile women with polycystic ovary syndrome (PCOS) and to determine beneficial effect of Metformin when taken during pregnancy. Methods: Metformin was started at an oral dose of 500mg/day and maintained at 1500mg/ day for 3 months in Group A(n=170) and 6 months in Group B(n=145). Then they were given ovulation induction medicines along with Metformin. Patients conceived were advised to take Metformin 750 mg/day in divided doses during the pregnancy. They were subdivided into Group I (those who continued Metformin during pregnancy) and Group II (those who did not continue Metformin during pregnancy. The parameters representing outcome of pregnancy such as live births, single births, multiple births, abortions, stillbirths, postnatal deaths, threatened abortions, pre term and post term delivery were observed. Results: Younger patients responded to the treatment in terms of conception which was not observed in the case of older infertile patients. Overall conceptions after three months treatment with Metformin were highly significantly low (p=0.0001) compared to those who were given Metformin for six months. Combination of Clomiphene citrate with Metformin and combination of Human Menopausal Gonadotrophin with Metformin resulted in 36.36% conceptions in Group A and 64.18 % in Group B. In patients who continued Metformin during pregnancy single live births were more in group I of Group A and Group B while still births were more in group II of Group A (p=0.011) and B (p=0.005). In patients who did not continue Metformin during pregnancy complications like threatened abortion and abortion (p=0.006) were found in Group A and (p=0.002) in Group B. Preterm delivery (p=0.048) was seen in Group A and (p=0.085) in Group B. Conclusion: Conceptions after six months treatment with Metformin were significant as compared to those given Metformin for three months. Metformin taken during the pregnancy duration improved the outcome of pregnancy